Lower airway collapse: Revisiting the definition and clinicopathologic features of canine bronchomalacia. (July 2021) - Reinero, Carol R.; Masseau, Isabelle
Highlights: Bronchomalacia is defined as dynamic collapse of segmental/subsegmental bronchi. It cannot be diagnosed using thoracic radiography but requires advanced imaging. Classification should score changes in airway caliber and functional impairment. Comorbid conditions, including other types of airway collapse, are common. No known direct treatment to reverse or delay progression of airway collapse exists. Abstract: Bronchomalacia (BM) is an inconsistently defined term in dogs, impairing understanding of clinical presentation, therapeutic response and prognosis. Herein the authors propose to clarify the definition of canine bronchomalacia (CBM) as regional to diffuse dynamic airway collapse of segmental and/or subsegmental bronchi with associated clinical signs due to airflow limitation. In contrast to tracheal collapse, mainstem bronchial collapse, and in some cases lobar collapse, CBM requires advanced imaging. Common co-morbid conditions (e.g., chronic bronchitis, mitral valve degenerative disease, etc.) should be identified during a comprehensive diagnostic evaluation. Current empiric treatments advocated in absence of clinical trials documenting efficacy in the dog warrant evaluation, as some (e.g., bronchodilators) may have detrimental effects in certain types of airway collapse in humans. There is no direct treatment for CBM, as defined above, but non-specific therapies and targeted treatment of co-morbid disease may improve clinical signs and quality of life. In this manuscript, the authors provide a review of the different types of airway collapse focusing on CBM, reviewing their definition and etiology, proposing a classification scheme, and discussing clinical signs, diagnostic testing, and treatment. Future studies should focus on both improving understanding of the etiology and natural disease progression of CBM and treatment trials.